Note on the lectotypification of Adenocalymma paulistarum (Bignoniaceae) - Arbo, Maria M. (Phytotaxa, 2017)
Adenocalymma paulistarum is a liana with yellow flowers that grows in semi-deciduous and humid forests from Southern South America. The study of Bignoniaceae type materials from species native to Argentina raised the need for a revision of the lectotypifications made by previous researchers in 2013 and 2014. Following ICN, the first lectotypification is to be superseded by the second one.